Retrospective observational study of atypical winter respiratory illness season using real-time syndromic surveillance, England, 2014-15 - Smith, S; Morbey, R; Pebody, R; Hughes, T; De Lusignan, S; Yeates, F; Thomas, H; O'Brien, S; Smith, G; Elliot, A (Centers for Disease Control and Prevention, 2017)
During winter 2014–15, England experienced severe strains on acute health services. We investigated whether syndromic surveillance could contribute to understanding of the unusually high level of healthcare needs. We compared trends for several respiratory syndromic indicators from that winter to historical baselines. Cumulative and mean incidence rates were compared by winter and age group. All-age influenza-like illness was at expected levels; however, severe asthma and pneumonia levels were above those expected. Across several respiratory indicators, cumulative incidence rates during 2014–15 were similar to those of previous years, but higher for older persons; we saw increased rates of acute respiratory disease, including influenza like illness, severe asthma, and pneumonia, in the 65–74- and >75-year age groups. Age group–specific statistical algorithms may provide insights into the burden on health services and improve early warning in future winters.